Catalytic steam co-gasification of biomass and coal in a dual loop gasification system with olivine catalysts. Issue 3 (June 2020) - Xiao, Yahui; Xu, Shaoping; Liu, Yong; Qiao, Congzhen
Abstract: A dual loop gasification system (DLG) has been previously proposed to facilitate tar destruction and H2 -rich gas production in steam gasification of biomass. To sustain the process auto-thermal, however, additional fuel with higher carbon content has to be supplied. Co-gasification of biomass in conjunction with coal is a preferred option. Herein, the heat balance of the steam co-gasification of pine sawdust and Shenmu bituminous coal in the DLG has been analyzed to verify the feasibility of the process with the help of Aspen Plus. Upon which, the co-gasification experiments in the DLG have been investigated with olivine as both solid heat carriers and in-situ tar destruction catalysts. The simulation results show that the self-heating of the DLG in the co-gasification is achieved at the coal blending ratio of 28%, gasification circulation ratio of 19 and reforming circulation ratio of 20 when the gasifier temperature 800 °C, reforming temperature 850 °C, combustor temperature 920 °C and S/C 1.1. The co-gasification experiments indicate that the tar is efficiently destructed in the DLG at the optimized reformer temperature and with olivine catalysts. Highlights: Co-gasification of biomass and coal studied in dual loop gasification system (DLG). Self-heating of DLG in co-gasification is achieved at coal blending ratio of 28%. Tar content is efficiently reduced to 13.1 g/Nm 3 in DLG with olivine as bed materials.